A connected history of audiovisual translation Sources and resources - Gambier Yves; Jin Haina (Routledge, 2025)
In the last 20 years, research in audiovisual translation has increased exponentially. The hallmark of most of the studies is descriptive. Now that the subfield is recognized within translation studies, it is time to research the background of the different practices and understand the impact of technology on them. Two main issues are raised in our chapter. Why do we need a history of audiovisual translation (AVT), especially between 1895 and the years 1950, when most of the countries selected a certain mode of AVT? The elements of such a history cannot be tackled outside of a history of cinema, understood both as an art made of techniques and a business. Our chapter is the culmination, sustained by various data, of our thoughts and reflections on the pressing need to write a coherent history of AVT. For the time being, many of the sources and resources are scattered. What kind of history is desirable? We try here to define the conditions and resources for a connected and comparative history and deal with a few methodological challenges. By way of illustration, we refer to diverse local situations in France, the UK, the US and China.
The Routledge Handbook of Translation and Media